Composite poly(ethylene carbonate) electrolytes with electrospun silica nanofibers. (19th October 2017) - Li, Zhenguang; Matsumoto, Hidetoshi; Tominaga, Yoichi
Abstract : We prepared a ternary composite polymer electrolyte from poly(ethylene carbonate) (PEC), lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) and non‐calcined silica nanofibers (SNFs) having 3 average diameters (300, 700, and 1000 nm). The SNF composite electrolytes were obtained as homogeneous, self‐standing membranes. The ionic conductivity of PEC/LiTFSI 100 mol% was increased by the addition of SNFs, and the thinner SNFs with average diameter 300 nm were most effective in improving the conductivity. The conductivity was of the order of 10 −4 S/cm at 60°C. The lithium transference number of the SNF300 composite was greater than 0.7. Stress‐strain curves of the composites indicated significant increases in Young's modulus and maximum stress for the PEC electrolytes. The 5% weight‐loss temperature of the composites also improved with the addition of SNF.